PERAN GURU DALAM PENANAMAN KARAKTER KEDISIPLINAN PADA ANAK USIA 5-6 TAHUN DI TK KANISIUS PONTIANAK UTARA - Lusiana Lusiana; Aunurrahman Aunurrahman; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research aims to describe teacher role in inculcating disciplined characters in children 5-6 years at Kanisius Kindergarten, North Pontianak. In this study using a method descriptive qualitative. The subject of this study is the teacher of class B2 and B3. Used data collection techniques namely interviews, observation and documentation. Data collection, data reduction, data presentation, and drawing conclusions are the data analysis used. Technique of checking the validity of the data using member check and triangulation. The research shows that result: 1. The role of teacher as a guide is to direct, guide behavior in a positive direction, see the involvement of children and help children who have difficulties. 2. The role of teacher as a motivator gives appreciation, encouragement and enthusiasm to children who have shown and children who have not shown the character of discipline. 3. The role of teacher as a facilitator is that the teacher provides services to children at any time. In this study it was concluded that the teacher’s role has been carried out in accordance with the teacher’s indicators as a guide, motivator, and facilitator.